2011
DOI: 10.1128/jcm.02571-10
|View full text |Cite
|
Sign up to set email alerts
|

Achromobacter xylosoxidans Infection Presenting as a Pulmonary Nodule Mimicking Cancer

Abstract: Achromobacter xylosoxidans is typically isolated from pulmonary sources, presenting as pneumonia in immunosuppressed individuals. We describe a novel clinical presentation of A. xylosoxidans infection presenting as multiple spiculated, pulmonary nodules mimicking cancer for which the patient underwent a wedge resection of the lung for diagnosis and staging of presumptive cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…Three sets of primers (VB1 to VB6) were used to amplify the 1,500-bp 16S rRNA gene, and the first set (VB1 and VB2) was used for the 500-bp 16S rRNA sequencing. The primers were as follows: VB1 (TGGAGAGTTTGATCCTG GCTCAG), VB2 (TACCGCGGCTGCTGGCAC), VB3 (CCAGCAGCCG CGGTAATAC), VB4 (CGGGACTTAACCCAACATCTCAC), VB5 (GTG AGATGTTGGGTTAAGTCCCG), and VB6 (AAGGAGGTGATCCAGCC GCA) (15,16). The sequences were analyzed and compared to information in the BIBI and GenBank databases (17).…”
Section: Methodsmentioning
confidence: 99%
“…Three sets of primers (VB1 to VB6) were used to amplify the 1,500-bp 16S rRNA gene, and the first set (VB1 and VB2) was used for the 500-bp 16S rRNA sequencing. The primers were as follows: VB1 (TGGAGAGTTTGATCCTG GCTCAG), VB2 (TACCGCGGCTGCTGGCAC), VB3 (CCAGCAGCCG CGGTAATAC), VB4 (CGGGACTTAACCCAACATCTCAC), VB5 (GTG AGATGTTGGGTTAAGTCCCG), and VB6 (AAGGAGGTGATCCAGCC GCA) (15,16). The sequences were analyzed and compared to information in the BIBI and GenBank databases (17).…”
Section: Methodsmentioning
confidence: 99%
“…The second most common was non-cystic fibrosis bronchiectasis (15% of cases). In perhaps the best review to date of achromobacterial lung disease in subjects with and without cystic fibrosis, Claasen and colleagues (11) found that the most common comorbidities affecting subjects without cystic fibrosis were malignancies (solid and hematologic) and immunoglobulin deficiencies. These findings parallel earlier work on Achromobacter bacteremia, which found higher prevalence rates among immunosuppressed subjects and those with underlying malignancy (10,19,55).…”
Section: Comorbiditiesmentioning
confidence: 98%
“…However, certain species, most notably xylosoxidans and denitrificans, can cause disease in certain patient populations, such as subjects with cystic fibrosis, hematologic and solid organ malignancies, renal failure, and immunodeficiencies (8)(9)(10)(11)(12). The most frequent clinical isolate is xylosoxidans, which can infect any number of organ systems, and is increasingly recognized as an important emerging nosocomial pathogen (13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 98%
“…34 , 35 It, like Burkholderia , has been isolated from aqueous solutions used in health-care facilities, including IV and dialysis solutions, and it can colonize medical equipment. 36 …”
Section: Th E Pathogensmentioning
confidence: 99%